PHOTOMETRICAL RESEARCH OF GSS «INTELSAT 10-02» - Sukhov, P. P.; Karpenko, G. F.; Epishev, V. P.; Motrunych, I. I. (Одеські астрономічні публікації, 2009)
On example of the studies the obtained coordinate and photometrical data GSS «Intelsat 10-02» is shown as possible surveillance with the help of ground-based optical facilities dynamic state satellite and his behaviors on orbit. The analysis of variation character of the light curves in B,V,R filters, time intervals between the flashes, the color indexes variation shows that the systems of stabilization of the platform, the transceiving antennas and the solar panels worked in operating normal mode during the dates of observation. The solar panels orientation relative to the Sun maintains well enough, rotated practically along the equtor plane tracking the Sun’s path (the Earth’s rotation). Orientation to axis of the rotation of the platform practically remains to be unchanged to direction on the centre of the masses of the Earth.